Manajemen Pembiayaan dan Pelaporan Keuangan Program Microfinance Syariah Berbasis Masyrakat (MISYKAT) di Lembaga Keuangan Mikro Syariah Baitul Mal Aceh - Nurul Fajri; Ridwan Ibrahim (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2016)
This research was conducted at the Institute of Islamic Microfinance Baitul Mal of Aceh, with the aim to determine the financial management practices of Community-Based Program Islamic Microfinance and financial reporting of financing Islamic Microfinance Community-Based Program.This research using descriptive analysis with an emphasis on understanding the issues based on the conditions of reality to explain the description in the form of the sentence, with the source of the data used are primary data obtained directly from the research. The results showed the distribution of funding for microfinance islamic community based on Micro Finance Institutions Sharia Baitul Mal Aceh distributed to mustahik to approach the concept of 5C + 1S, which includes character, ability / capacity, capital, collateral and economic situation / condition, with the number of mustahik financing receiver as much as 2,083 people with average growth rate of as much as 694 people per year mustahik, and the amount of financing provided as much as Rp 7.963.850.000,- the rate of growth of an annual average of Rp 2,654,616,667, -. Financial reporting conducted by Microfinance Institutions Sharia Baitul Mal of Aceh are in accordance with the statement of financial accounting standards (SFAS) No. 101 concerning the presentation of the financial statements of sharia, which includes the statement of financial position (balance sheet), income / loss, cash flow statement and notes financial statements (CALK). Keywords: Islamic Microfinance Financing and Financial Reporting